2020
DOI: 10.21603/2308-4057-2020-1-76-83
|View full text |Cite
|
Sign up to set email alerts
|

Improved technology for new-generation Kazakh national meat products

Abstract: Introduction. Extract of goji berries (Lycium Barbarum L.) and buckwheat flour (Fagopýrum esculéntum L.) possess antioxidant and antimicrobial properties. As a result, they can be used to improve traditional Kazakh horse-meat formulations to obtain functional cooked and smoked meat products. These natural biologically active substances can improve the oxidative stability of pigments, lipids, and proteins of finished products. The research objective was to assess the potential of goji extract and buckwheat flou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Two studies employing flavonoids extracted from L. barbarum leaves in different proportions (0.5, 1.0, and 1.5%) mixed with minced mutton meat indicated that they could significantly inhibit lipid oxidation and myofibrillar proteins oxidation and could therefore be utilized as a natural antioxidant for meat preservation ( 58 , 59 ). The same results were found in a study conducted on horse meat products injected with 1.0% of GB extract ( 62 ). A combination of dried GBs and pumpkin powder has shown, on the cooked and smoked beef filet, the maintenance of the quality, sensory properties, color characteristics, and prevention of oxidative changes, even with a reduced amount of nitrites ( 60 ).…”
Section: Goji Effects On Meat Qualitysupporting
confidence: 84%
“…Two studies employing flavonoids extracted from L. barbarum leaves in different proportions (0.5, 1.0, and 1.5%) mixed with minced mutton meat indicated that they could significantly inhibit lipid oxidation and myofibrillar proteins oxidation and could therefore be utilized as a natural antioxidant for meat preservation ( 58 , 59 ). The same results were found in a study conducted on horse meat products injected with 1.0% of GB extract ( 62 ). A combination of dried GBs and pumpkin powder has shown, on the cooked and smoked beef filet, the maintenance of the quality, sensory properties, color characteristics, and prevention of oxidative changes, even with a reduced amount of nitrites ( 60 ).…”
Section: Goji Effects On Meat Qualitysupporting
confidence: 84%
“…Despite isolated outbreaks of Aujeszky’s disease in pigs, over the past months of 2020, there are no signs that may indicate a serious risk of reoccurrence and spread of this dangerous disease in the agricultural lands of the Republic of Kazakhstan. According to the Minister of Agriculture of Kazakhstan, Saparkhan Omarov, all regions of the republic are currently provided with the necessary veterinary preparations by more than 97% of the declared annual need ( Vaal, 2020 ; Uzakov et al ., 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…According to the data presented in (Vaal, 2020;Uzakov et al, 2020). At the same time, the minister noted that in the procurement of preparations, preference is given to products of domestic manufacturers over foreign supplies.…”
Section: Modern Trends In the Development Of Aujeszky's Disease And Imentioning
confidence: 99%
“…Goji extract has been successfully incorporated in products of minced catfish [ 164 ] and horse meat [ 165 , 166 ] to improve sensory properties and oxidative stability during storage. Moreover, chitosan/goji extract can be used as a biopreservative and antilisterial agent when mixed with minced catfish [ 164 ].…”
Section: Goji Berry As Source Of Functional Ingredients In Different ...mentioning
confidence: 99%